2008
DOI: 10.1007/s00249-008-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

SANS/SAXS study of the BSA solvation properties in aqueous urea solutions via a global fit approach

Abstract: We report on the solvation properties and intermolecular interactions of a model protein (bovine serum albumine, BSA) in urea aqueous solutions, as obtained by combining small-angle neutron and X-ray scattering experiments. According to a global fit strategy, all the whole set of scattering curves are analysed by considering a unique model which includes the BSA structure, the protein-protein interactions and the thermodynamic exchange process of water/urea molecules at the protein solvent interface. As a main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…The fitted volume fraction values are systematically higher and the surface charges are 16 to 20 e. These results are in good agreement with our previous study using SAXS as well as those reported in the literature. 20,36 It is interesting to see that for 0.5 M NaSCN, the data with 89.4 mg mL À1 BSA are better described using a screened Coulomb potential, indicating that the surface charge still plays a role. The higher surface charge (36.6 e) can be explained by the strong salting-in effect of the thiocyanate anion.…”
Section: Protein-protein Interaction From the Second Virial Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitted volume fraction values are systematically higher and the surface charges are 16 to 20 e. These results are in good agreement with our previous study using SAXS as well as those reported in the literature. 20,36 It is interesting to see that for 0.5 M NaSCN, the data with 89.4 mg mL À1 BSA are better described using a screened Coulomb potential, indicating that the surface charge still plays a role. The higher surface charge (36.6 e) can be explained by the strong salting-in effect of the thiocyanate anion.…”
Section: Protein-protein Interaction From the Second Virial Coefficientmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Using SANS combined with SAXS, Sinibaldi et al studied the solvation properties of BSA and lysozyme in urea solution and water/glycerol mixtures, respectively. 19,20 SANS and SAXS provide complementary information due to the different responses to the hydration shell surrounding proteins. The interpretation of SANS data requires knowledge of the hydration level and the H-D exchange ratio of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their easy accessibility, high stability, ability to bind various ligands and similarity to HSA, mammalian serum albumins, especially bovine serum albumin (BSA), are utilized in kinetic and affinity drug tests as replacements for HSA, as well as in many biochemical and pharmacological applications (Sohl & Splittgerber, 1991). BSA is used as a standard in many procedures, including vaccine preparation, as a drug by itself and as a test antigen to check the validity of assays (Leong & Fox, 1988), as a molecular-weight standard (Peters, 1996;Birnbaum & Nilsson, 1992;Sinibaldi et al, 2008) and in immunological tests such as ELISA and others (Herzog et al, 1983). ESA can replace BSA in radioimmunological and immunoenzyme analyses and its use in virological practice has been raised (Chan & Porter, 1967).…”
Section: Applications Of Albuminsmentioning
confidence: 99%
“…Small-angle scattering of x-rays (SAXS) and neutrons (SANS) are particularly suited to probe the structural properties of hydration layers around biomacromolecules in solution (28)(29)(30)(31)(32)(33). SAXS and SANS are sensitive to the electronic and nuclear scattering-length density (SLD) fluctuations, Dr, respectively, between solutes (i.e., biomacromolecules) and the bulk solvent (29).…”
Section: Introductionmentioning
confidence: 99%
“…SAXS and SANS have the advantage that the respective contribution of the hydration layer (or shell) to the overall scattering from the macromolecules varies both in magnitude and sign (34). The HS contribution has been implemented in a number of programs to back-calculate SAXS (and, more rarely, SANS) curves from atomic structures, either as a homogeneous shell of a specific thickness (30)(31)(32)35), as grid elements (36,37), as dummy atoms (38,39), as explicit water molecules (40)(41)(42)(43)(44)(45), as a density map (46,47), or by voxelization (48). Accurate description of the HS is essential for the growing field of quasiatomic protein-structure modeling from solution data (34).…”
Section: Introductionmentioning
confidence: 99%